The Difference and Significance of Parietal Pleura Invasion and Rib Invasion in Pathological T Classification With Non-Small Cell Lung Cancer - Wu, Lei-Lei; Li, Chong-Wu; Li, Kun; Qiu, Li-Hong; Xu, Shu-Quan; Lin, Wei-Kang; Ma, Guo-Wei; Li, Zhi-Xin; Xie, Dong (Frontiers in Oncology, 2022)
Objective: This study was to explore the difference and significance of parietal pleura invasion and rib invasion in pathological T classification with non-small cell lung cancer. Methods: A total of 8,681 patients after lung resection were selected to perform analyses. Multivariable Cox analysis was used to identify the mortality differences in patients between parietal pleura invasion and rib invasion. Eligible patients with chest wall invasion were re-categorized according to the prognosis. Cancer-specific survival curves for different pathological T (pT) classifications were presented. Results: There were 466 patients considered parietal pleura invasion, 237 patients served as rib invasion. Cases with rib invasion had poorer survival than those with the invasion of parietal pleura (adjusted hazard ratio [HR]= 1.627, P =0.004). In the cohort for parietal pleura invasion, patients with tumor size ≤5cm reached more satisfied survival outcomes over patients with tumor size >5cm (unadjusted HR =1.598, P =0.006). However, there was no predictive difference in the cohort of rib invasion. The results of the multivariable analysis revealed that the mortality with parietal pleura invasion plus tumor size ≤5cm were similar to patients with classification pT3 (P =0.761), and patients for parietal pleura invasion plus tumor size >5cm and pT4 had no stratified survival outcome (P =0.809). Patients identified as rib invasion had a poorer prognosis than patients for pT4 (P =0.037). Conclusions: Rib invasion has a poorer prognosis than pT4. Patients with parietal pleura invasion and tumor size with 5.1-7.0cm could be appropriately up-classified from pT3 to pT4.